Factors associated with treatment retention in pregnant women with opioid use disorders prescribed methadone or electing non-pharmacological treatment. Issue 1 (2nd January 2020) - Jancaitis, Brandi; Kelpin, Sydney; Masho, Saba; May, James; Haug, Nancy A.; Svikis, Dace
ABSTRACT: Opioid use during pregnancy is rising, with an estimated 14–22% of women obtaining an opioid prescription during pregnancy. Methadone maintenance therapy (MMT) has been the gold standard for treatment of opioid use disorders during pregnancy; however, its use is limited in clinical practice due to availability, stigma, and reluctance on the part of clinicians. The present study compared against medical advice (AMA) treatment dropout from seven days of residential care between pregnant women diagnosed with opioid dependence who elected either MMT (n = 119) or non-pharmacological treatment (NPT) (n = 91) within the same treatment program in Baltimore, Maryland from 1996 to 1998. Multiple logistic regression analysis was conducted to compare the rate of AMA drop out between the two modalities. Patients who elected NPT were 2.77 times as likely to leave residential treatment as patients who elected MMT (adjusted odds ratio [OR = 2.77, 95% confidence interval [CI]: 1.23–6.17]. AMA was associated with interviewer-assessed drug severity and patient's rating of the importance of psychiatric treatment. The present findings further support the clinical utility of MMT and suggest that policies that facilitate the implementation of MMT in clinical practice would be beneficial to the engagement and retention of pregnant women with opioid use disorders.